2017
DOI: 10.1007/s13149-017-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

À propos de 98 cas de dengue hospitalisés dans une clinique privée de Ouagadougou : aspects épidémiologiques, diagnostiques et évolutifs

Abstract: Extremely widespread, the dengue is a reemerging infectious disease. In Burkina Faso, dengue is a reality that was little known. The aim of this study was to study epidemiology, diagnostic and outcomes of dengue patients in Ouagadougou. A retrospective study covered a period of two years, from 1 January 2013 to 31 December 2014 in a private clinic in Ouagadougou. Patients included in the study were hospitalized for fever and painful syndrome with a positive test to the dengue non-structural antigen 1 (NS1 Ag).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The average age of the patients was 29 years with a sex ratio of 0.9. These results are comparable to those of previous studies in an epidemic context [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average age of the patients was 29 years with a sex ratio of 0.9. These results are comparable to those of previous studies in an epidemic context [6].…”
Section: Discussionsupporting
confidence: 91%
“…In the diagnostic strategy for dengue in Burkina Faso, any patient presenting with acute fever and a negative RDT (Rapid Diagnostic Test) for malaria or a positive RDT for malaria not responding to anti-malarial treatment with signs of arboviruses is subjected to a rapid immunochromatographic test for dengue "Dengue Duo (NS1 Ag+IgM/IgG) SD (Stantard Diagnostics) Bioline". A patient who is positive for this test (positive Ig M and/or Ig G serology and/or positive NS1 antigen) should have blood drawn for confirmation by positive Ig M serology (ELISA), or increased Ig G titres or virus detection by PCR or isolation [4][5][6].…”
Section: Biological Tests For Denguementioning
confidence: 99%
“…Dengue fever is often confused with malaria, as the symptoms of the two diseases are similar, but taking antimalarial drugs can worsen the condition of a patient with dengue fever [28]. Unfortunately, even though recent studies have reported the presence of the dengue virus in Ouagadougou, the capital of Burkina Faso [29,30], many cases of dengue continue to be misdiagnosed and improperly treated [22,31]. Very few health workers have received training on dengue fever or non-malaria febrile diseases [21,22].…”
Section: Dengue In Burkina Faso (West Africa)mentioning
confidence: 99%
“…Over the past two decades, the average annual number of cases of dengue haemorrhagic fever has risen dramatically [1], with a sixfold increase in incidence from 1990 to 2013 [2]. Unfortunately, many cases of dengue fever continue to be misdiagnosed and improperly treated [3]. Dengue fever is often confused with malaria because the symptoms of the two diseases are similar, sometimes leading to misdiagnosis with potentially fatal outcomes.…”
Section: Introductionmentioning
confidence: 99%